Sistem Informasi Tabungan Siswa (Sitasi) Berbasis Website Dengan Model PIECES - Azzah Rifqi Hakim; Abimanyu Surya Putra; Nikmatul Maula; Cindy Ayu Santika; Dea T rinanda Prameswari; Rousyati Rousyati; Fandhillah Fandhillah; Husni Mubarok; Dzulchan Abror; Warjiyono Warjiyono; Ulumuddin Ulumuddin (LPPM UBSI Kampus Kota Tegal, 2023)
Student savings is a form of activity that aims to educate students about the importance of saving and good financial management. Student savings also help students prepare for the future, develop savings habits, and understand the importance of discipline in managing finances. This study discusses the development of a website-based Student Savings Information System (Citation) as a solution to replace the manual student savings system at Nurul Iman Islamic Vocational School. Stasi uses information technology and the internet to facilitate the management of student savings. This system provides advantages and convenience for educational institutions, teachers, students, and parents. The research method used includes data collection through direct observation and the application of the PIECES Analysis method (Performance, Information, Economy, Control/Security, Efficiency, Service). This method is used to process data relevant to research. With the existence of a website-based Student Savings Information System (SITAS), it is hoped that the management of student savings can become more efficient, transparent, and provide greater benefits for students, teachers, and educational institutions as a whole. Through Citation, students can learn about the importance of saving and managing finances responsibly from an early age.